Therapeutic imaging window of cerebral infarction revealed by multisequence magnetic resonance imaging: An animal and clinical study☆ - Lu, Hong (Medknow Publications & Media Pvt Ltd, 2012)
In this study, we established a Wistar rat model of right middle cerebral artery occlusion and observed pathological imaging changes (T2-weighted imaging [T(2)WI], T(2)FLAIR, and diffusion-weighted imaging [DWI]) following cerebral infarction. The pathological changes were divided into three phases: early cerebral infarction, middle cerebral infarction, and late cerebral infarction. In the early cerebral infarction phase (less than 2 hours post-infarction), there was evidence of intracellular edema, which improved after reperfusion. This improvement was defined as the ischemic penumbra. In this phase, a high DWI signal and a low apparent diffusion coefficient were observed in the right basal ganglia region. By contrast, there were no abnormal T(2)WI and T(2)FLAIR signals. For the middle cerebral infarction phase (2–4 hours post-infarction), a mixed edema was observed. After reperfusion, there was a mild improvement in cell edema, while the angioedema became more serious. A high DWI signal and a low apparent diffusion coefficient signal were observed, and some rats showed high T(2)WI and T(2)FLAIR signals. For the late cerebral infarction phase (4–6 hours post-infarction), significant angioedema was visible in the infarction site. After reperfusion, there was a significant increase in angioedema, while there was evidence of hemorrhage and necrosis. A mixed signal was observed on DWI, while a high apparent diffusion coefficient signal, a high T(2)WI signal, and a high T(2)FLAIR signal were also observed. All 86 cerebral infarction patients were subjected to T(2)WI, T(2)FLAIR, and DWI. MRI results of clinic data similar to the early infarction phase of animal experiments were found in 51 patients, for which 10 patients (10/51) had an onset time greater than 6 hours. A total of 35 patients had MRI results similar to the middle and late infarction phase of animal experiments, of which eight patients (8/35) had an onset time less than 6 hours. These data suggest that defining the “therapeutic time window” as the time 6 hours after infarction may not be suitable for all patients. Integrated application of MRI sequences including T(2)WI, T(2)FLAIR, DW-MRI, and apparent diffusion coefficient mapping should be used to examine the ischemic penumbra, which may provide valuable information for identifying the “therapeutic time window”.